Available nutrients and labile carbon fractions in soil irrigated with sodic water - Rathi, Deepika; Devraj, Devraj; Antil, R S; Ramprakash, Ramprakash; Sharma, M K (The Indian Journal of Agricultural Sciences, 2020)
An ongoing long-term field experiment established in the year 1994 at Vegetable Science Research Farm, CCS HAU, Hisar, India under different vegetable cropping systems was selected to study the effects of sodic water irrigation, gypsum and farmyard manure on labile soil organic carbon fractions and available nutrients in soil. The present study was conducted after 20 years of experimentation during 2014-2015. The field was irrigated with high RSC (11.5 me/l) sodic water having three treatment levels each of gypsum, viz G0 control, G1=50 % neutralization of RSC, G2=100% neutralization of RSC, as well as FYM (F0 = control, F1= 10 tons/ha, F2 =20 tons/ha) in a sandy loam Typic Ustochrept. Results showed that the pH of soil was very high under F0G0, and it decreased with the use of FYM and gypsum as amendments, however a reverse trend was observed in electrical conductivity. There was an increase in different carbon fractions and available nutrients when FYM was applied over no FYM application. Application of gypsum increased microbial biomass carbon, light fraction carbon and available nutrients (N, P, S) content in the soil but dissolved organic carbon and available K content was found decreased. It can be concluded that application of FYM @20 t/ha along with gypsum @100% neutralization of RSC of irrigation water should be applied for maintaining soil quality and productivity.